Analiza dimenzij "globoke" integracije v poročanju treh slovenskih časnikov o zadevah EU v času predsedovanja Slovenije Svetu EU - Čepič, Mitja (Družboslovne razprave, 2009)
A content analysis of three Slovenian daily newspapers, two general and one financial, during the period of the Slovenian Presidency of the Council of the EU sought to investigate the role of the three dimensions of "deep" European integration: functional, territorial and affiliational, within newspaper discourse. The analysis shows that, while all three dimensions have their place in public debate, their discursive representation lacks important elements. The reporting on EU issues is domesticated in terms of size and position in the medium, but at the same time it invokes scepticism regarding its role in the formation of Europe as a special imagined community.
Keywords: European Union; Evropska unija; Predsedstva; Presidency; Mass media; Množični mediji; Newspapers; Časniki; Analiza vsebine; Content analysis; Slovenia; Slovenija; poročanje; predsedovanje